2021
DOI: 10.3389/fgene.2021.636934
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes and MicroRNAs Associated With Idiopathic Pulmonary Arterial Hypertension by Integrated Bioinformatics Analyses

Abstract: ObjectiveThe aim of this study is the identification of hub genes associated with idiopathic pulmonary arterial hypertension (IPAH).Materials and MethodsGSE15197 gene expression data was downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified by screening IPAH patients and controls. The 5,000 genes with the greatest variances were analyzed using a weighted gene co-expression network analysis (WGCNA). Modules with the strongest correlation with IPAH were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we analyzed all the publicly available independent experimental RNA-Seq datasets—on transcriptomes from the tissues of hypertensive versus normotensive patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], hypertensive versus normotensive animals [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], and domestic versus wild animals [ 72 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong H et al identi ed CSF3R, NT5E, ANGPT2, FGF7 and CXCL9 as candidate biomarkers of PAH, and ruxolitinib might exert promising therapeutic action for PAH[28]. Qiu X et al performed a WGCNA on GSE15197 and found 11 real hub genes, including EP300, MMP2, CDH2, CDK2, GNG10, ALB, SMC2, DHX15, CUL3, BTBD1, and LTN1, were over-expressed in IPAH[29]. Contrastly, Liu J et al suggested that 10 hub genes were determined via Cytohubba and a crucially ceRNA network was identi ed, including 14 LncRNAs, 2 miRNAs, and 3 mRNAs[30].…”
mentioning
confidence: 99%